2015
DOI: 10.1080/10503307.2015.1072285
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sex and gender in ten types of psychotherapy

Abstract: Since the results show that therapists differ substantially with regard to their intervention techniques due to their sex, they should become more conscious of their interventions by considering patients' severity of psychological problems and patients' level of psychological functioning so as to not over or underchallenge them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 37 publications
0
17
0
3
Order By: Relevance
“…Why would male therapists experience more countertransference than female therapists? Staczan et al ( 2017 ) found gender-related differences in therapeutic technique where male therapists tended to make more confrontative interventions, that is, interpretations of defense and resistance, whereas female therapists tended to intervene more on an empathic and supportive level. The gender difference is doubtless a complex issue, but one possible understanding of the gender difference in countertransference is that more emphasis on confrontative interventions evokes more reactions in the therapist (and presumably also in the patient) than if the therapist takes a more empathic stance.…”
Section: Discussionmentioning
confidence: 99%
“…Why would male therapists experience more countertransference than female therapists? Staczan et al ( 2017 ) found gender-related differences in therapeutic technique where male therapists tended to make more confrontative interventions, that is, interpretations of defense and resistance, whereas female therapists tended to intervene more on an empathic and supportive level. The gender difference is doubtless a complex issue, but one possible understanding of the gender difference in countertransference is that more emphasis on confrontative interventions evokes more reactions in the therapist (and presumably also in the patient) than if the therapist takes a more empathic stance.…”
Section: Discussionmentioning
confidence: 99%
“…Una primera limitación a considerar de la presente investigación, es que la composición de la muestra es en un 62% femenina. En la actualidad sabemos que el procesamiento emocional y la diferencia de género debe ser considerado ya que es un tema que sigue abierto a la investigación y debate a la luz de evidencia (Staczan et al, 2017).…”
Section: Discussionunclassified
“…Sample 3 was recruited in a project on outpatients promoted by the Swiss Charta for Psychotherapy. The aim of this nonrandomized field study is to investigate various process-outcome aspects of outpatient treatments carried out with different experiential or psychodynamic therapy methods [ 26 28 ]. Cases from this sample were selected using the following criteria: At least one Axis I disorder according to the criteria of DSM-IV.…”
Section: Methodsmentioning
confidence: 99%